Understanding the Antibody Repertoire in Neuropsychiatric Systemic Lupus Erythematosus and Neuromyelitis Optica Spectrum Disorder: Do They Share Common Targets?. Issue 2 (9th January 2018) - Mader, Simone; Jeganathan, Venkatesh; Arinuma, Yoshiyuki; Fujieda, Yuichiro; Dujmovic, Irena; Drulovic, Jelena; Shimizu, Yuka; Sakuma, Yuko; Stern, Joel N. H.; Aranow, Cynthia; Mackay, Meggan; Yasuda, Shinsuke; et al.
Abstract : Objective: IgG anti‐DWEYS antibodies cross‐reactive with DNA and the N ‐methyl‐d ‐aspartate receptor subunits GluN2A and GluN2B are known to be associated with neuropsychiatric systemic lupus erythematosus (NPSLE). IgG anti‐DWEYS have not been investigated in demyelinating NPSLE or in another demyelinating disorder, neuromyelitis optica spectrum disorder (NMOSD), which is a disease also found mainly in young women and associated with aquaporin 4 (AQP‐4) or myelin oligodendrocyte glycoprotein (MOG) antibodies. This study was undertaken to investigate the frequency of all of these brain‐reactive antibodies in patients with NPSLE, those with demyelinating NPSLE, and those with NMOSD. Methods: Serum samples from patients with NPSLE (n = 108), patients with SLE without neuropsychiatric manifestations (n = 38), patients with NMOSD (n = 33), and healthy controls (n = 106) were assessed for the frequency of IgG anti‐brain antibodies as well as IgG antibodies to AQP‐4, MOG, GluN2A/GluN2B, and double‐stranded DNA (dsDNA). Results: Sera were positive for IgG anti–AQP‐4 antibodies in 27 (82%) of 33 patients with NMOSD and 3 (27%) of 11 patients with demyelinating NPSLE, whereas all sera from patients with non‐demyelinating NPSLE, patients with SLE, and healthy controls were negative for IgG anti–AQP‐4. IgG anti‐MOG were detected at high titers in 3 (50%) of 6 patients with NMOSD who were negative for IgG anti–AQP‐4, and at low titers in 2 (18%) of 11 patients with demyelinating NPSLE and 1 (1%) of 97 patients with non‐demyelinating NPSLE. IgG antibodies to dsDNA were present in 11 (33%) of 33 patients with NMOSD. Only 4 (12%) of 33 patients with NMOSD were positive for IgG anti‐DWEYS, compared to 11 (29%) of 38 patients with SLE and 59 (55%) of 108 patients with NPSLE. IgG anti‐DWEYS antibodies were present in 56 (58%) of 97 patients with non‐demyelinating NPSLE and 3 (27%) of 11 patients with demyelinating NPSLE. Serum IgG brain‐reactive antibodies were present at a similar frequency in patients with non‐demyelinating NPSLE (72 [75%] of 96), those with demyelinating NPSLE (9 [82%] of 11), and those with SLE (32 [84%] of 38), but were less frequent in patients with NMOSD (20 [61%] of 33). Conclusion: Patients with demyelinating NPSLE should be tested for IgG antibodies to AQP‐4, MOG, and DWEYS. IgG anti–AQP‐4 can be considered diagnostic for NMOSD, whereas none of these antibodies appear to be diagnostic for demyelinating NPSLE. Moreover, IgG anti‐dsDNA are present in patients with NMOSD but are not cross‐reactive with IgG anti‐DWEYS, indicating that the antigenic stimulus and mechanisms of tissue damage are potentially different between demyelinating NPSLE and NMOSD.